Dietary lysophospholipids enhance broiler performance, immune response, meat quality, and mitigate oxidative stress - Eid, Yahya; El-Soud, Sabria A.; Gamel, Mostafa Z.; El-Kassas, Seham; Azzam, Mahmoud M.; Di Cerbo, Alessandro; Elolimy, Ahmed A.; Alagawany, Mahmoud; Kirrella, Abeer A. (Frontiers in Immunology, 2025)
BackgroundThe current study evaluated the impact of lysophospholipid emulsifiers’ (LPLs) dietary incorporation on ameliorating the negative impacts of oxidative stress in broilers.MethodsA total of 270 2-week-old male Avian 48 chicks were randomly divided into six experimental groups. The first group fed a basal diet (BD) only, while the second group (+DEX) received BD containing 2 mg/kg dexamethasone. The third and fourth groups consisted of birds fed a BD containing 0.5 and 1 g of LPLSs/kg, respectively. The fifth and sixth groups, received BD containing 1 mg/kg dexamethasone and were supplemented with 0.5 and 1 g of LPLs, respectively.ResultsSeparate supplementation of LPLs significantly improved the broilers’ growth as confirmed by increasing final weight, body gain, and FI with improved feed conversion ratio (FCR) (P < 0.05). LPLs also improved the carcass yield (carcass, breast, and thigh muscle percentages, P = 0.0001) and meat quality (water-holding capacity, P < 0.05; tenderness, P < 0.05; pH, P < 0.001; and color, P < 0.05), with notable improvement in intestinal and liver histology and significantly increased intestinal villi length and width (P < 0.001). Furthermore, LPLs improved the serum levels of globulin (P < 0.01), creatinine (P < 0.001), LDL cholesterol (P < 0.001), HDL cholesterol (P < 0.01), and triglycerides (P < 0.001). Immune and antioxidant levels, as well as LPLs’ dietary supplementation, distinctly increased the phagocytic activity and index, total antioxidants, superoxide dismutase, catalase, and glutathione peroxidase, with a marked reduction in malondialdehyde (MDA) (P < 0.05). However, feeding dexamethasone negatively impacted the birds’ performance, confirmed by a marked retardation of the birds’ growth as manifested by lowering final body weight, gain, and increasing FCR, along with poor carcass yield and increased abdominal fat accumulation (P < 0.05). The dexamethasone-associated negative impacts were ameliorated with the combined LPL dietary supplementation.ConclusionDietary supplementation of LPLs at 0.5g level could effectively mitigate the adverse effects of oxidative stress in broilers, improving the growth performance, immune response, intestinal health, and meat quality of broiler chickens under normal and stressful conditions.